Assessment of Bite Force in Patients with Periodontitis Before and after Splinting in Anterior Teeth using Computerised Occlusal Analysis System: A Clinical Study - Sathyalakshmi Ravikumar; Dhanvanthraj Venkatesan; Tarunkumar Kanmani; Rajalakshmi Ashokkumar; Vamsi Lavu (Journal of Clinical and Diagnostic Research)
Introduction: Bite force is a measure of the functional status of the masticatory system. It is determined by the combined activity of the jaw elevator muscles, which are influenced by reflex mechanisms and jaw biomechanics. Measuring bite force can yield valuable information for assessing the activity and function of the jaw muscles. Recording devices and techniques are important factors in obtaining bite force measurements. Aim: To compare the occlusal function in terms of changes in bite force parameters before and after the splinting of periodontally weakened anterior teeth using the NUPAI bite scan (Fuji™) method in patients with stage I and II periodontitis. Materials and Methods: This prospective clinical study was conducted in the Department of Periodontology at Sri Ramachandra Dental College and Hospital, Chennai, Tamil Nadu, India between May 2023 and February 2024. The bite force parameters assessed included pressed area, average pressure, and maximum pressure using the NUPAI bite scan (Fuji™) in a total of 25 individuals before and after extracoronal splinting of periodontally weakened anterior teeth. Statistical analysis was performed using IBM Statistical Package for Social Sciences (SPSS) version 20.0, and data were summarised as mean and standard deviation. A paired t-test was conducted to find significant differences in the various variables within the group. A p-value of less than 0.05 was considered statistically significant. Results: Maximum bite pressure and average bite pressure were found to be greater after the procedure of extracoronal splinting compared to before splinting, with mean values of 26.59±4.32 MPa (before splinting) and 30.45±4.29 MPa (after splinting) (p-value=0.005), and 9.11±1.75 MPa (before splinting) and 9.86±1.83 MPa (after splinting) (p-value=0.015), respectively. However, the mean pressed area before and after the splinting procedure was 22.76±34.49 mm² and 19.00±19.40 mm², respectively, showing no statistically significant difference between them (p-value=0.323). It can be inferred that, without appreciably altering the contact area, the splinting technique successfully increased bite force by improving both maximum and average pressures. Conclusion: The present study concluded that the splinting procedure used in phase I therapy aids in improving the patient’s occlusal function, and the NUPAI bite scan system allows for quantitative recording of this improvement.